OVERVIEW OF BLOOD SUGAR LEVELS WHEN USING THE POINT OF CARE TESTING (POCT) METHOD - Dewi Herlyana Putri; Ni Komang Eva Dwi Yanti; Ni Luh Yesi Pratami; Wandy Christiawan Lampaga; Agung Surya Rahman; Moh Arif; Saskirana; Fitri Aramadani; Novita Fitri Fajriani; Mujizat (PT. Radja Intercontinental Publishing, 2026)
Blood glucose level is an important indicator used to assess the body’s metabolic condition and detect the risk of diabetes mellitus. University students are considered vulnerable to unhealthy lifestyle changes, including irregular eating patterns, lack of physical activity, academic stress, and insufficient sleep, which may affect blood glucose regulation. This study aimed to describe random blood glucose levels using the Point-Of-Care Testing (POCT) method among students of the Medical Laboratory Technology Study Program, Class of 2025, at Politeknik Cendrawasih Palu. This research employed a descriptive study with a cross-sectional approach. The sample consisted of 34 students who met the inclusion criteria. Blood glucose examination was performed using a POCT glucometer with capillary blood samples obtained from the fingertip. The results showed that all respondents had random blood glucose levels within the normal range, with values ranging from 89–161 mg/dL and an average level of 110.41 mg/dL. These findings indicate that the respondents generally had good glucose metabolism. The POCT method proved to be practical, rapid, and effective for early blood glucose screening and health monitoring among students.